Effect of Nitrogen Fertilizer on Nitrogen Accumulation, Translocation, and Use Efficiency in Dryland Oilseed Flax. (1st September 2015) - Xie, Yaping; Gan, Yantai; Li, Yang; Niu, Junyi; Gao, Yuhong; An, Huihui; Li, Airong
Abstract : Oilseed flax ( Linum usitatissimum L.) yields are primarily fertilizer‐limited, especially by N supply in the semiarid regions of North China. This study was conducted to determine whether N accumulation, translocation and N use efficiency (NUE) could be manipulated through N. The effects of N on N translocation, oilseed flax yield, oil content and NUE were studied at Zhangjiakou, China. Plants were grown at 0, 45, 90, and 135 kg N ha −1 (designated as the control, low N, moderate N, and high N, respectively), in 2011 and 2012. We found that N accumulation in leaves and capsule pericarps reached the maximum at anthesis and kernel developmental stage, respectively, then decreased rapidly before maturity. Averaged over 2 yr, N translocation from leaves to the seeds increased by 43, 150, and 150% under low N, moderate N, and high N, respectively, compared to the control; similarly, N translocation in capsule pericarps increased by 43, 243, and 190%, respectively. We discovered that leaves contributed the largest proportion of the seed N (averaging 80% in both years), and secondarily by the capsule pericarp N, which contributed 12% (in 2011) and 9% (in 2012) of the seed N. The highest seed yields were 2270 kg ha −1 (in 2011) and 1903 kg ha −1 (in 2012) which were obtained with the moderate N. Oil content was not affected by N. Nitrogen use efficiency decreased with progressively higher rates of N. The results suggest the moderate‐N supply was adequate for promoting N translocation, and increasing N harvest index, NUE, and the productivity of oilseed flax.